P3-S7.08 Clinical evaluation of the APTIMA®Trichomonas vaginalis assay on the TIGRIS® DTS® system in asymptomatic and symptomatic female subjects. (10th July 2011) - Schwebke, J; Hobbs, M; Taylor, S; Chapin, K; Catania, M; Weinbaum, B; Getman, D; Gaydos, C
Abstract : Background: This study evaluated the clinical performance of the APTIMA® Trichomonas vaginalis (ATV, Gen-Probe Incorporated) Assay, a nucleic acid amplification test for the diagnosis of Trichomonas vaginalis (TV) infection, in asymptomatic and symptomatic women. Methods: This prospective, multicenter clinical trial enrolled 1025 women attending US OB-GYN, adolescent, family planning, or sexually transmitted disease clinics. Four specimen types were collected from each subject: physician-collected vaginal swab, endocervical swab, ThinPrep specimen, and first-catch urine. Of three vaginal swabs collected from each subject, one was used for wet mount microscopic examination, one for culture, and one for molecular testing for TV. The order of collection for each vaginal swab sample was rotated to minimise sampling bias. Each specimen was tested by ATV assay using the automated TIGRIS DTS system. ATV assay performance in each sample type was determined by comparing ATV assay test result to the patient infected status (positive in saline wet mount and/or culture) for each sample. Results: Of 933 subjects included in the analysis, 59.9% were symptomatic. Compared to patient infected status, ATV assay clinical sensitivities and specificities were 100% and 99.0%, respectively, from vaginal swabs; 100% and 99.4%, respectively, from endocervical swab; 100% and 99.6%, respectively, from ThinPrep specimens; and 95.2% and 98.9%, respectively, from patient-collected urine samples. ATV assay performance was similar in asymptomatic and symptomatic patients, by age group (14–17 years and 18 years or older), and was consistent between testing sites. The ATV assay also demonstrated superior performance compared to wet mount microscopic examination and TV culture, regardless of the specimen type utilised. Conclusions: This study provides clinical validation of the ATV assay for the intended uses of detecting TV rRNA in asymptomatic women, and/or to aid in the diagnosis of trichomoniasis in symptomatic women, in a US population. The use of highly accurate, fully-automated molecular tests such as the ATV assay for testing easily obtained vaginal swab and urine samples should facilitate large-scale screening for TV in the US.